Stereochemistry of C18 Monounsaturated Cork Suberin Acids Determined by Spectroscopic Techniques Including 1H-NMR Multiplet Analysis of Olefinic Protons - Santos, Sara; Graça, José (Phytochemical Analysis, 2014)
Introduction Suberin is a biopolyester responsible for the protection of secondary plant tissues, and yet its molecular structure remains unknown. The C18:1 ω-hydroxyacid and the C18:1 α,ω-diacid are major monomers in the suberin structure, but the configuration of the double bond remains to be elucidated. Objective To unequivocally define the configuration of the C18:1 suberin acids. Methods Pure C18:1 ω-hydroxyacid and C18:1 α,ω-diacid, isolated from cork suberin, and two structurally very close C18:1 model compounds of known stereochemistry, methyl oleate and methyl elaidate, were analysed by NMR spectroscopy, Fourier transform infrared (FTIR) and Raman spectroscopy, and GC–MS. Results The GC–MS analysis showed that both acids were present in cork suberin as only one geometric isomer. The analysis of dimethyloxazoline (DMOX) and picolinyl derivatives proved the double bond position to be at C–9. The FTIR spectra were concordant with a cis-configuration for both suberin acids, but their unambiguous stereochemical assignment came from the NMR analysis: (i) the chemical shifts of the allylic 13C carbons were shielded comparatively to the trans model compound, and (ii) the complex multiplets of the olefinic protons could be simulated only with 3JHH and long-range 4JHH coupling constants typical of a cis geometry. Conclusion The two C18:1 suberin acids in cork are (Z)-18-hydroxyoctadec-9-enoic acid and (Z)-octadec-9-enedoic acid. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: (Z)-18-hydroxyoctadec-9-enoic acid; (Z)-octadec-9-enedoic acid; 1H-NMR multiplet analysis; Cis/trans configuration; cork suberin

Glycerol-derived ester oligomers from cork suberin. - Graça, José; Santos, Sara (Chemistry and physics of lipids, 2006)
The cork suberin polyester was partially depolymerized by a methanolysis reaction catalyzed by calcium hydroxide. The methanolisate was analysed by ESI-MS/MS in the form of [M+Li](+) adduct-ions. This reaction solubilized a mixture of monomers and oligomers, including a set of glycerol-derived dimeric and trimeric esters. Four types of glycerol esters were identified: monoacylglycerols of alpha,omega-diacids, of omega-hydroxyacids and of monoacids; diglycerol diesters of alpha,omega-diacids; diacylglycerols of alpha,omega-diacids; monoacylglycerols of linear dimeric esters of alpha,omega-diacids and omega-hydroxyacids. The alpha,omega-diacids and omega-hydroxyacids found as monomer residues in the glycerol esters are the main ones found as cork suberin monomers. It is concluded that suberin is a glycerol-derived lipid of polymeric dimensions. Due to the protective and insulating role that it plays in plants, suberin should be considered together with the other known glycerolipids that build up biological membranes.
The following values have no corresponding Zotero field: accession-num: 16979606
Keywords: a-o-Diacids; Cork; ESI-MS/MS analysis; Glycerolipids; o-Hydroxyacids; suberin

Glycerol-derived ester oligomers from cork suberin. - Graça, José; Santos, Sara (Chemistry and physics of lipids, 2006)
The cork suberin polyester was partially depolymerized by a methanolysis reaction catalyzed by calcium hydroxide. The methanolisate was analysed by ESI-MS/MS in the form of [M+Li](+) adduct-ions. This reaction solubilized a mixture of monomers and oligomers, including a set of glycerol-derived dimeric and trimeric esters. Four types of glycerol esters were identified: monoacylglycerols of alpha,omega-diacids, of omega-hydroxyacids and of monoacids; diglycerol diesters of alpha,omega-diacids; diacylglycerols of alpha,omega-diacids; monoacylglycerols of linear dimeric esters of alpha,omega-diacids and omega-hydroxyacids. The alpha,omega-diacids and omega-hydroxyacids found as monomer residues in the glycerol esters are the main ones found as cork suberin monomers. It is concluded that suberin is a glycerol-derived lipid of polymeric dimensions. Due to the protective and insulating role that it plays in plants, suberin should be considered together with the other known glycerolipids that build up biological membranes.
Keywords: a-o-Diacids; Cork; ESI-MS/MS analysis; Glycerolipids; o-Hydroxyacids; suberin

Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara (Biomacromolecules, 2006)
Cork suberin was partially depolymerized by methanolysis catalyzed by calcium hydroxide. Analysis by GC-MS of the methanolysate showed suberin monomers, including glycerol and long-chain α,?-diacids and ?-hydroxyacids. ESI-MS analysis of the methanolysate showed, besides the aliphatic monomers, suberin oligomers, including linear dimeric esters of α,?-diacids and ?-hydroxyacids. Two types of dimeric esters were identified:? a α,?-diacid linked to a ?-hydroxyacid and two inter-linked ?-hydroxyacids. The α,?-diacids and ?-hydroxyacids found as monomer residues in the dimeric esters were mainly the C18 monomers with midchain substituents. The identification of these dimeric esters was based in their CID-MS/MS spectra and confirmed after synthesis of model compounds. The occurrence of inter-esterified long-chain monomers in suberin brings a new insight in the understanding of the polyester structure of this biopolymer.
From Duplicate 1 (Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara)
Keywords: cork suberin; dimeric esters; Dimerization; Electrospray Ionization; Electrospray Ionization: metho; Esters; Esters: chemistry; GC-MS (voyant); Lipids; Mass; Membrane Lipids; Membrane Lipids: chemistry; Molecular Structure; Sensitivity and Specificity; Spectrometry; Trees; Trees: chemistry